Model Bimbingan Konseling dengan Pendekatan Cognitive Behavioral Therapy (CBT) di Pesantren - Asep Rahmatullah; Akhmad Fauzi Hamzah (Program Studi Bimbingan dan Konseling Islam, 2025)
Human behavioral deviations stem from cognitive dysfunction that requires improvement through approaches such as Cognitive-Behavior Therapy (CBT) with an emphasis on self-efficacy. This phenomenological qualitative study aims to fill the research gap by investigating the application of the pesantren-based guidance and counseling (BK) model at the Moderate Islamic Boarding School At -Thohiriyah Banten, where the results show that the integration of CBT techniques (such as cognitive restructuring) with Islamic values (such as muhasabah and tazkiyatun nafs) is supported by the communal pesantren environment and the charismatic figure of the Kyai. but faces obstacles such as counselor competency gaps, stigma towards mental health issues, and hierarchical culture. Therefore, it is concluded that the effectiveness of this model depends on strategic efforts such as counselor training and adaptation of techniques that respect the local wisdom of Islamic boarding schools.